Поліуретан-епоксидні композиції з підвищеними механічними властивостями для реконструктивних операцій у щелепно-лицьовій хірургії - Галатенко, Н.А.; Куксін, А.М.; Рожнова, Р.А.; Астапенко, О.О. (Видавничий дім "Академперіодика" НАН України, 2007)
New polyurethane-epoxy biodegraded polymeric compositions with osteotropic action are developed. The reactive oligomer-oligomer and oligomer-polymer mixtures containing urethane fragments, drug substances, and hydroxyapatite are used to obtain composition materials. Such composition design provides the solution of post-operation complication problems and the bioactivity-biocompatibility of the composition. The dependences of mechanical properties of the composition material on the polyurethane/epoxy oligomer ratio, polyurethane molecular mass, urethane group concentration, and hydroxyapatite content are analyzed.